Outcome of pregnancy in patients with autoimmune rheumatic disease before the disease onset. Issue 12 (December 1988) - Siamopoulou-Mavridou, A; Manoussakis, M N; Mavridis, A K; Moutsopoulos, H M
Abstract : The outcomes of 419 pregnancies of 154 unselected patients with various auto-immune diseases, including 390 pregnancies before the disease onset, were studied retrospectively. The patients comprised 40 with systemic lupus erythematosus (SLE), 72 with rheumatoid arthritis, 21 with primary Sjögren's syndrome (1 degree SS), 14 with progressive systemic sclerosis (PSS), and seven with mixed connective tissue disease. The histories of 267 pregnancies of 98 healthy, age matched women served as controls. Our data indicate that compared with healthy controls autoimmune patients do not experience a higher incidence of fetal loss. The incidence of fetal loss before disease onset in the various groups of autoimmune patients (as well as after disease onset in patients with SLE and RA) was not significantly different from that of controls. Spontaneous abortions in patients with 1 degree SS and PSS before disease onset occurred significantly more frequently (p less than 0.05) than in controls. Nevertheless, it should be noted that this was not the case when the incidence per woman was considered. On the other hand, patients with SLE, both before and after disease onset, experienced a higher incidence of premature deliveries (p less than 0.05). Finally, the analysis of autoantibody profiles, including antibodies to nuclear antigens, to Ro(SSA) cellular antigen, to double stranded DNA, and to cardiolipin, could not demonstrate any association of autoantibodies with any particular pregnancy outcome.